2003
DOI: 10.4049/jimmunol.171.10.5071
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Lymphocytes Regulating Th2 Pathology Escape Neonatal Tolerization

Abstract: Transplantation tolerance induced by neonatal injection of semiallogeneic spleen cells is associated in several strain combinations with a pathological syndrome caused by Th2 differentiation of donor-specific CD4+ T lymphocytes. We investigated the role of host CD8+ T cells in the regulation of this Th2 pathology. IgE serum levels and eosinophilia significantly increased in BALB/c mice neonatally injected with (A/J × BALB/c)F1 spleen cells when CD8+ T cells were depleted by administration of anti-CD8 mAb or wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…29 Additionally, accumulation of eosinophils in the lung is exacerbated by CD8 depletion in mouse models of RSV infection 30 and allergic asthma. 31 Observations such as these have lead to a resurgence in the study of putative CD8-positive regulatory or suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, accumulation of eosinophils in the lung is exacerbated by CD8 depletion in mouse models of RSV infection 30 and allergic asthma. 31 Observations such as these have lead to a resurgence in the study of putative CD8-positive regulatory or suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the neonates, we and other investigators reported that regulatory CD8 + T cells controlling Th2 pathology are effective (20,21). In both cases, the induction of IFN-g-producing CD8…”
mentioning
confidence: 97%
“…Neutralization of IL-4 significantly decreased the percentages of all these donor cell types without completely eliminating them. We next investigated the effects of early neutralization of IL-4 on the Th2-type pathology induced by neonatal alloimmunization (19). As expected, F 1 -treated mice developed splenomegaly and produced high levels of serum IgE when compared to untreated mice ( Figure 1D).…”
Section: Perinatal Neutralization Of Il-4 Prevents Neonatal Transplanmentioning
confidence: 65%
“…The injection of (A/J x BALB/c) F 1 spleen cells into BALB/c neonates induces lymphoid chimerism, immune polarization and transplantation tolerance of donor-type skin allografts (9,(18)(19)(20). We first evaluated the effects of perinatal administration of anti-IL-4 mAb on neonatal transplantation acceptance and Th2-type responses.…”
Section: Perinatal Neutralization Of Il-4 Prevents Neonatal Transplanmentioning
confidence: 99%